Disrupted Delivery: Demythifying Remote and Online Instruction in Times of Crisis and Emergency. (December 2021) - Brunner, Brigitta R.; Mutsvairo, Bruce
This is the guest editors' essay for the Special Issue: Disrupted Delivery: Remote and Online Instruction in Times of Crisis and Emergency, Guest Editors: Brigitta R. Brunner & Bruce Mutsvairo.